1997
DOI: 10.1016/s0014-5793(97)00755-2
|View full text |Cite
|
Sign up to set email alerts
|

Tissue‐dependent upregulation of rat uncoupling protein‐2 expression in response to fasting or cold

Abstract: The control of uncoupling protein-2 (UCP2) mRNA expression in rat brown adipose tissue (BAT), heart and skeletal muscles was examined. Cold exposure (48 h) increased UCP2 mRNA in BAT, heart and soleus muscle by 2.4-, 4.3-and 2.6-fold, respectively. Fasting (48 h) had no effect on UCP2 mRNA expression neither in BAT nor in heart, but markedly increased it in skeletal muscles. While the upregulation of UCP2 mRNA in response to cold exposure is in line with a putative uncoupling role for this protein in thermoreg… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

25
155
1
2

Year Published

1999
1999
2010
2010

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 215 publications
(183 citation statements)
references
References 12 publications
(18 reference statements)
25
155
1
2
Order By: Relevance
“…Another candidate seems free fatty acid. UCP2 and UCP3 expression in skeletal muscle have been reported to increase in response to fasting [1,8] , which is a representative cue to elevate plasma free fatty acids. The present results showed that administration of CL produced a sustained elevation of plasma free fatty acids as a result of their potent lipomobilizing action on adipose tissues [19,24].…”
Section: Discussionmentioning
confidence: 99%
“…Another candidate seems free fatty acid. UCP2 and UCP3 expression in skeletal muscle have been reported to increase in response to fasting [1,8] , which is a representative cue to elevate plasma free fatty acids. The present results showed that administration of CL produced a sustained elevation of plasma free fatty acids as a result of their potent lipomobilizing action on adipose tissues [19,24].…”
Section: Discussionmentioning
confidence: 99%
“…In vivo studies indicate that physiological and pathological elevation of blood long-chain fatty acids (up to 2-to 3-fold) resulting from fasting (16,(47)(48)(49)(50), high fat diet (12), suckling of newborn pups (51), sepsis (52), or streptozotocin-induced diabetes (53, 54) induce up-regulation of Ucp2. Similarly, in vitro studies have shown that monounsaturated (n-9) and polyunsaturated (n-6 and n-3) fatty acids can dramatically induce up-regulation of Ucp2 in 3T3-L1 preadipocytes (55), human primary cultured myotubes (56), the rat myoblast cell line L6 (57), the rat insulinoma cell line INS-1 (58, 59), rat primary cultured adipocytes (60), and cloned bovine mammary epithelial cells (61).…”
Section: Regulation By Long-chain Fatty Acidsmentioning
confidence: 99%
“…Animal models suggest that many tissues, including brown adipose tissue (Boss et al 1997;Denjean et al 1999;Yamashita et al 1999), white adipose tissue (Yamashita et al 1999), heart (Boss et al 1997), soleus muscle (Boss et al 1997), spinal cord (Mizuno et al 2000), and spleen (Ganta et al 2006) do indeed display at least some changes in gene expression in response to cold. Hypothermia can also modify gene expression responses to ischemia/reperfusion of brain (Fukui et al 2006;Kobayashi et al 2008;Ohta et al 2007;Yenari and Han 2006) and liver (Niemann et al 2010).…”
Section: Introductionmentioning
confidence: 99%
“…In the spleen, changes in cytokine and chemokine expression occur even after sympathetic denervation, suggesting that cold itself, and not the increase in sympathetic activity that occurs during hypothermic exposure, may be responsible for some of the changes seen (Ganta et al 2006). The importance of examining different tissues is illustrated by the observation that in rat (Boss et al 1997;Mizuno et al 2000), UCP-2 responses to hypothermia appear to vary somewhat as a function of tissue type.…”
Section: Introductionmentioning
confidence: 99%